2010
DOI: 10.1038/onc.2010.475
|View full text |Cite
|
Sign up to set email alerts
|

Diverse mechanisms of Wnt activation and effects of pathway inhibition on proliferation of human gastric carcinoma cells

Abstract: Human gastric carcinomas are among the most treatment refractory epithelial malignancies. Increased understanding of the underlying molecular aberrations in such tumors could provide insights leading to improved therapeutic approaches. In this study, we characterized diverse genetic aberrations leading to constitutive Wnt signaling activation in a series of human gastric carcinoma cell lines. Downregulation of TCF signaling by stable transduction of dominant negative TCF-4 (DNTCF4) resulted in inhibition of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
(65 reference statements)
3
11
0
Order By: Relevance
“…We further confirmed that direct inhibition of WNT pathway down-stream effector TCF/LEF activity via a dominant negative TCF4 (Dn-TCF4) construct (23) can recapitulate the functional phenotypes of proliferation repression and G2/M arrest induced by SOX11 forced expression. Using Granta-519 (Figure 4D, 4E) and Z138 (Supplementary Figure S5A, S5B) cell lines, we showed that DN-TCF4 transfected cells (orange) exhibited significant proliferative arrest (Figure 4D, Supplementary Figure S5A) compared to control plasmid transfected cells (green).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…We further confirmed that direct inhibition of WNT pathway down-stream effector TCF/LEF activity via a dominant negative TCF4 (Dn-TCF4) construct (23) can recapitulate the functional phenotypes of proliferation repression and G2/M arrest induced by SOX11 forced expression. Using Granta-519 (Figure 4D, 4E) and Z138 (Supplementary Figure S5A, S5B) cell lines, we showed that DN-TCF4 transfected cells (orange) exhibited significant proliferative arrest (Figure 4D, Supplementary Figure S5A) compared to control plasmid transfected cells (green).…”
Section: Resultssupporting
confidence: 62%
“…SMAD3 reporter construct (SMAD3p-Luc) containing SOX11 consensus sequence was kindly gifted by Dr. Thomas J. Kelly (49). DN-TCF4 was a kind gift by Dr. Stuart A. Aaronson (23) and was subsequently cloned into an expression vector containing IRES-eGFP (Ex-M60) for overexpression experiment. SOX11 siRNA sequences were listed in supplementary table 8.…”
Section: Methodsmentioning
confidence: 99%
“…Although exogenously applied Wnt3a has great potential as a therapeutic protein, safety remains a primary concern. The delivery of high concentrations of potent growth factors to a skeletal injury site carries with it potential oncological risk to the patient 50 . To circumvent issues associated with prolonged or uncontrolled exposure to a growth factor, we delivered L-Wnt3a ex vivo.…”
Section: L-wnt3a Restores Osteogenic Capacity To Bone Grafts From Agementioning
confidence: 99%
“…The AGS cell line was derived from human gastric adenocarcinoma. The Ī²ā€catenin gene in AGS cells contains an activating mutation that results in the unregulated proliferation of the cells (Asciutti, Akiri, Grumolato, Vijayakumar, & Aaronson, ). Because Cby functions as a Ī²ā€catenin antagonist, we examined the effect of Cby overexpression on Ī²ā€catenin levels and cell growth in AGS cells.…”
Section: Resultsmentioning
confidence: 99%